Perspektif Yuridis Kedudukan Perbankan Sebagai Pengelola Dana Kartu Uang Elektronik (Electronic Money) Terkait Dengan Perlindungan Konsumen - Fontian Munzil (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2017)
The development of information technology, especially in the business world is growing rapidly including payment innovation has changed from physical cash to non-physical electronics that are very dynamic. Electronic money also called e-money is a product that has shifted the role of cash in trading. Financial Industry has a large role as an issuer of electronic money cards and consumers are card users including the role of the National Banking Authority. The problem that will be examined by the writer is what is the legal standing of the Bank as the manager of public funds for the ownership of funds in electronic money card? and how far the laws reaches legal protection for the Bank's consumers on the ownership of electronic money? This study uses a normative juridical approach that is used to analyze the research data including also examining vertical and horizontal synchronization of the relevant laws and regulations. Research specifications are descriptive analysis to provide data that is as accurate as possible and actual. The stages of library research collect data obtained from secondary data using primary, secondary and tertiary legal materials. The results of the study found, first, the legal standing of the Bank as a manager of third party fund sourced from electronic money has been clearly regulated by laws in the banking sector except the treatment of the status of customer fund electronic money which recorded at the Bank unlike treatment of third party fund that are guaranteed by LPS, secondly, laws cannot reach maximum legal protection against electronic money card holder losses, balance in standard clause agreements, guarantee funds for electronic money by LPS, and in particular ownership of unregistered electronic money cards based on cardholders.